Evapotranspiração e eficiência do uso da água no primeiro ciclo produtivo da figueira 'Roxo de valinhos' submetida a cobertura morta - Souza, Adilson Pacheco de; Silva, Andrea Carvalho da; Leonel, Sarita [UNESP]; Souza, Manoel Euzebio de; Tanaka, Adriana Aki (Univ Federal Uberlandia, 2014)
Evaluated the evapotranspiration (ETc) and the efficiency of water use (USA) by the fig tree 'Purple Valinhos' submitted to irrigation and mulching (bagacilho of sugar cane crushed) in the first production cycle, at conditions of Botucatu, St. Paul. We used the method of soil water balance and to obtain the reference evapotranspiration method was used Montheit FAO Penman 56. For the assessment of crop coefficients (kc) we adopted the following phenological distribution: phase 1 - between transplanting and 20% of the vegetative (DV), ii) phase 2 - 20 to 80% DV, and iii) phase 3 - fruiting. Observe the cumulative ETc 409.4 and 465.8 mm in 254 days after transplanting (DAT) and averages of 1.47 and 1.67 mm day(-1), with and without mulching (CC and SC). The crop coefficients (kc) mediums were 0.16, 0.43 and 0.49 for SC and 0.18, 0.44 and 0.50 for CC, in phases 1 and 3, respectively. The EUA values decrease with increasing the volume of water received and ranged between 1.65 and 3.32 kg of green figs per m(3) of water for irrigated SC and CC.

Avaliou-se a evapotranspiração (ETc) e a eficiência do uso da água (EUA) pela figueira ‘Roxo de Valinhos’ submetida à irrigação e cobertura morta (bagacilho de cana-de-açúcar triturado) no primeiro ciclo produtivo, nas condições edafoclimáticas de Botucatu, São Paulo. Empregou-se o método do balanço hídrico do solo e para a obtenção da evapotranspiração de referência foi utilizado o método Penman Montheit FAO 56. Para a avaliação dos coeficientes de cultivo (kc) adotou-se a seguinte distribuição fenológica: fase 1 - entre o transplantio e 20% do desenvolvimento vegetativo (DV); ii) fase 2 - de 20 a 80% DV; e iii) fase 3 – frutificação. Observam-se ETc acumulados de 409,4 e 465,8 mm em 254 dias após o transplantio (DAT) e médias de 1,47 e 1,67 mm dia-1, com e sem cobertura morta (CC e SC). Os coeficientes de cultivo (kc) médios foram de 0,16; 0,43 e 0,49 para SC e de 0,18; 0,44 e 0,50 para CC, entre as fases 1 e 3, respectivamente. Os valores de EUA diminuem com o aumento do volume de água recebido e variaram entre 1,65 e 3,32 kg de figos verdes por m3 de água irrigada para SC e CC.
Evapotranspiration and eficience of water use in first production cicle of the fig tree 'Roxo de Valinhos' under mulching
Keywords: Crop coefficients; Irrigation Management; Ficus Carica